2005
DOI: 10.1016/j.jms.2004.08.019
|View full text |Cite
|
Sign up to set email alerts
|

The rotationally-resolved absorption spectrum of formaldehyde from 6547 to 6804cm−1

Abstract: Access to the full text of the published version may require a subscription. Rights AbstractThe room temperature absorption spectrum of formaldehyde, H 2 CO, from 6547 to 6804 cm −1 (1527 to 1470 nm) is reported with a spectral resolution of 0.001 cm −1 . The spectrum was measured using cavity-enhanced absorption spectroscopy (CEAS) and absorption cross-sections were calculated after calibrating the system using known absorption lines of H 2 O and CO 2 . Several vibrational combination bands occur in this reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 18 publications
(19 reference statements)
0
33
0
Order By: Relevance
“…CH 2 O has been quantified using cw-CRDS at around 6600 cm À1 in two recent publications [27,28] and both studies were in rather large disagreement with the absorption cross sections reported by Staak et al [24]. CH 2 O has been identified by Djehiche et al [27] as a product in the photolysis of CH 3 ONO.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…CH 2 O has been quantified using cw-CRDS at around 6600 cm À1 in two recent publications [27,28] and both studies were in rather large disagreement with the absorption cross sections reported by Staak et al [24]. CH 2 O has been identified by Djehiche et al [27] as a product in the photolysis of CH 3 ONO.…”
Section: Introductionmentioning
confidence: 88%
“…They have determined the absorption cross section of one absorption line under their experimental conditions (24 mbar air) using a commercial, calibrated standard cylinder of CH 2 O (Air Liquide): the cylinder was labeled at 100 ppm, however an analysis using the well-known DNPH/ HPLC method revealed a concentration of only 40 ± 4 ppm. Extrapolation of the obtained absorption cross section to the conditions used by Staak et al [24] (2 mbar CH 2 O), assuming a Voigt profile and applying the broadening coefficients for N 2 and CH 2 O such as obtained by Staak et al [24], leads to a line strength a factor of 2 smaller. However, broadening coefficients for the different bath gases are not known with high precision, so the comparison is somewhat arguable.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…H 2 CO lines broadened by H 2 CO, N 2 and O 2 (E) (Staak et al 2005). HCO + lines broadened by He and Ar (T) (Buffa 2007).…”
Section: Broadening and Shift Of Molecular Linesmentioning
confidence: 99%
“…The experimental off-axis CEAS set-up is essentially the same as the one described in [58], [59]. The length of the optical cavity (Layertec mirrors: r = -2 m, R ~ 0.997) was 113 cm and the volume enclosed by the sample chamber was approximately 2 dm 3 .…”
Section: Off-axis Cavity Enhanced Absorption Setupmentioning
confidence: 99%